MARINE GEOLOGICAL RESEARCH OF UKRAINIAN SCIENTISTS IN THE ANTARCTIC - POLOVKA, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article deals with the results of the research conducted in the Antarctic expeditions by marine geologists of the Academy of Sciences of Ukrainian SSR (now National Academy of Sciences of Ukraine).